Effects of traditional Chinese herb hot compress combined with therapeutic exercise on pain, proprioception, and functional performance among older adults with knee osteoarthritis: A randomized controlled trial - Wang, Jingwen; Liu, Wei; Fu, Haitao (Frontiers in Physiology, 2022)
Background: Knee osteoarthritis (KOA) is one of the most common chronic progressive diseases with degenerative destruction of articular cartilage and bone, leading to knee pain, impaired proprioception, and reduced functional performance. This study was to investigate the effects of an 8-week Traditional Chinese herb hot compress (TCHHC) combined with therapeutic exercise (TE) on pain, proprioception, and functional performance among older adults with KOA. Methods: Twenty-seven older adults with KOA were recruited and randomly assigned to the TCHHC+TE or TE groups. Thirteen participants received TCHHC+TE, and fourteen received TE. At pre- (week 0) and post-intervention (week 9), their pain, joint proprioception, and functional performance were measured. Two-way ANOVA with repeated measures was adopted to analyze the data. Results: Compared with week 0, the pain score, proprioception thresholds of knee extension and ankle plantarflexion, and the times of TUG and 20-m walk tests decreased more significantly in the TCHHC+TE group than in the TE group at week 9. Conclusion: Compared with TE, the 8-week TCHHC+TE was superior in relieving pain, recovering proprioception, and improving functional performance among older adults with KOA. It is recommended that TCHHC should be adopted prior to TE to enhance the effects of KOA rehabilitation.